Again and Always: Intertextuality outside of Postmodernism - Simon Radchenko (Interlitteraria, 2022)
Intertextuality became one of the most popular and important terms in the culture of the 20th century. It is usually considered in connection with postmodernism and its ironic nature. Contemporary writing is still intertextual, though far from being postmodern. Moreover, even some medieval texts appear to operate intertextual tools systematically. The article presents examples of intertextuality in different novels from both the pre-postmodern and post-postmodern worlds, and searches for a possible explanation for this phenomenon through methodical solutions that would improve our understanding of intertextuality in the frame of literature analysis. It shows that different features of intertextual writing should be carefully considered in the frame of post-postmodern literature and questions the accuracy of our approach to discussing cultural process.